Regional rules in the global trading system - Estevadeordal, Antoni; Suominen, Kati; Teh, Robert 1954- (Cambridge University Press, 2009)
The proliferation of regional trade agreements (RTAs) over the past two decades has highlighted the need to look closely at the potential conflicts between regional and WTO rules or disciplines. A major obstacle to advancing understanding of RTAs is the absence of detailed information about their contents. This has limited the debate between those who view RTAs as discriminatory instruments hostage to protectionist interests and those who see them as conducive to multilateral trade opening. This book provides detailed analysis of RTA rules in six key areas - market access, technical barriers to trade, contingent protection, investment, services and competition policy - across dozens of the main RTAs in the world. The analysis helps to provide new insights into the interplay between regional and multilateral trade rules, advances understanding of the economic effects of RTAs and contributes to the discussion on how to deal with the burgeoning number of RTAs
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: International trade; Regionalism / Economic aspects; Trade blocs; Foreign trade regulation; Commercial treaties